Viral Marketing, Fear of Missing Out and Impulsive Buying Behavior Among Gen Z in Jakarta - Zulvia Khalid; Thilini De Silva; Panca Maulana; Iis Torisa Utami (Universitas Mercu Buana, 2025)
Objectives: This study is aimed at investigating the effects of viral marketing) on impulsive buying behavior mediated by fear of missing out (FoMO) among Gen Z customers in Indonesia.Methodology: This study adopts a quantitative method with cross-sectional design, including 209 Gen Z students from universities in Jakarta which were gathered using Purposive snowball sampling. Data were analyzed using structural equation modeling (SEM) with Partial Least Squares method to evaluate the validity of theoretical framework and to examine the proposed hypotheses.Finding: The findings demonstrate that viral marketing significantly affects the emergence of FoMO which mediates the relationship between viral marketing and impulsive buying behavior.Conclusion: The results are beneficial for marketers who aim to reach Gen Z and deal with the social and economic effects of inappropriate customer behavior that can happen when viral marketing campaigns are used too much. Gen Z will also become more aware and conscious if they learn these facts. This will help them resist the desire to buy things on impulse that viral marketing campaigns use to get customers to buy things.